2009
DOI: 10.1007/s00213-009-1582-8
|View full text |Cite
|
Sign up to set email alerts
|

Selective mu- and kappa-opioid receptor antagonists administered into the nucleus accumbens interfere with rapid tolerance to ethanol in rats

Abstract: Taken together, our results suggests that mu-opioid receptors in both shell and core portions of the nucleus accumbens, and possibly kappa-opioid in the core, participate in the modulation of rapid tolerance to ethanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…The stock solutions were stored at 4°C until use. Our previous results and others have indicated that the appropriate microinjection dosage for naloxonazine, naltrindole and nor -binaltorphimine to selectively block μ-, δ- and κ-opioid receptors, without interaction with other opioid receptor subtypes, is within 20 μg [9,10,20,21]. In current study, naloxone, naloxonazine, naltrindole and nor -binaltorphimine were microinjected at the dose of 10 μg/μl, which efficiently exhibits their effect of pharmacological blockade according to our previous studies [9,10].…”
Section: Methodsmentioning
confidence: 99%
“…The stock solutions were stored at 4°C until use. Our previous results and others have indicated that the appropriate microinjection dosage for naloxonazine, naltrindole and nor -binaltorphimine to selectively block μ-, δ- and κ-opioid receptors, without interaction with other opioid receptor subtypes, is within 20 μg [9,10,20,21]. In current study, naloxone, naloxonazine, naltrindole and nor -binaltorphimine were microinjected at the dose of 10 μg/μl, which efficiently exhibits their effect of pharmacological blockade according to our previous studies [9,10].…”
Section: Methodsmentioning
confidence: 99%
“…The stock solutions were stored at 4°C until use. Our previous results and others indicated that the appropriate microinjection dosage for naloxonazine, naltrindole and nor -binaltorphimine to selectively block μ-, δ- and κ-opioid receptors, without interaction with other opioid receptor subtypes, is within 20 μg [ 10 , 11 , 24 , 25 ]. In current study, naloxone, naloxonazine, naltrindole and nor -binaltorphimine were microinjected at the dose of 10 μg/μl, which efficiently exhibits their specific pharmacological blockade according to our previous studies [ 10 , 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…The stock solutions were stored at 4°C until use. Our previous results and others have indicated that the appropriate microinjection dosage for naloxonazine, naltrindole, and nor -binaltorphimine to selectively block μ -, δ -, and κ -opioid receptors, without interaction with other opioid receptor subtypes, is within 20  μ g [11, 17, 18]. In current study, naloxone, naloxonazine, naltrindole, and nor -binaltorphimine were microinjected at three different doses, 0.1, 1.0, and 10  μ g/ μ L. The total volume used for each microinjection was 1  μ L.…”
Section: Methodsmentioning
confidence: 99%